2005
DOI: 10.1111/j.1600-6143.2005.00892.x
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of CXCR3+ and CCR5+ T Cells and Production of Interferon-γ-Inducible Chemokines in Rejecting Human Arteries

Abstract: 1 These authors contributed equally to this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 37 publications
2
52
0
1
Order By: Relevance
“…[32][33][34] We have reached similar conclusions with our investigations in a chimeric human-animal model in which human coronary arteries are interposed into the aortae of severe combined immunodeficient (SCID) mouse hosts that are subsequently reconstituted with allogeneic human peripheral blood mononuclear cells. 35 In this model, intimal expansion and outward vascular remodeling in response to allogeneic human T cells is dependent on IFN-␥, 36 neutralization of IFN-␥ can prevent T cell-mediated EC and VSMC dysfunction, 37 IFN-␥-inducible chemokine production by vascular cells is associated with the recruitment of T H 1 cells, 38 and immunosuppressive agents that prevent intimal expansion also reduce IFN-␥ synthesis and responses. 39 Finally, administration of human IFN-␥ alone, in the absence of leukocytes, is sufficient to induce arteriosclerosis in the transplanted human arteries.…”
Section: Evidence For a Pathogenetic Role Of Ifn-␥ In Gamentioning
confidence: 99%
See 1 more Smart Citation
“…[32][33][34] We have reached similar conclusions with our investigations in a chimeric human-animal model in which human coronary arteries are interposed into the aortae of severe combined immunodeficient (SCID) mouse hosts that are subsequently reconstituted with allogeneic human peripheral blood mononuclear cells. 35 In this model, intimal expansion and outward vascular remodeling in response to allogeneic human T cells is dependent on IFN-␥, 36 neutralization of IFN-␥ can prevent T cell-mediated EC and VSMC dysfunction, 37 IFN-␥-inducible chemokine production by vascular cells is associated with the recruitment of T H 1 cells, 38 and immunosuppressive agents that prevent intimal expansion also reduce IFN-␥ synthesis and responses. 39 Finally, administration of human IFN-␥ alone, in the absence of leukocytes, is sufficient to induce arteriosclerosis in the transplanted human arteries.…”
Section: Evidence For a Pathogenetic Role Of Ifn-␥ In Gamentioning
confidence: 99%
“…A pathway of selective recruitment, judged by selective CXCR3-binding chemokine expression, does appear to operate in human GA, [23][24][25][26][27] as well as in our human artery GA model. 38 These studies have demonstrated that CXCR3 and CCR5 ligands are synthesized in both the parenchymal and vascular compartments of human cardiac allografts. However, a direct comparison of the production of IFN-␥-inducible chemokines by microvascular ECs (parenchymal versus large artery adventitial microvessels) and large artery luminal ECs has not been performed; such a comparison may be informative about the mechanisms responsible for selective accumulation of T H 1 cells in the vascular compartment during the pathogenesis of GA. T-cell recruitment may be species specific because many EC molecules that are involved in interactions with T cells show species differences.…”
Section: T H 1 Effector Cells and Cd8mentioning
confidence: 99%
“…IP-10 is one of chemokines toward CXCR3, has a chemotaxis for monocytes and Th1 cells, and is produced by fibroblasts and vascular endothelial cells, [26][27][28] while CXCR3 and CCR5 are specific chemokine receptors for Th1 cells. 29,30 The expression of both Th1 chemokines and chemokine receptors in the oral lesions indicates that Th1 cells possibly migrate there from the circulation.…”
Section: Cytokines Chemokines and Chemokine Receptors Involvement Inmentioning
confidence: 99%
“…Vários estudos observaram que a expressão dos receptores CXCR3 e CCR5 está aumentada na inflamação com fenótipo 1, como ocorre na DPOC 19,53,66 69 . Essas células expressavam CXCR3 e CCR5.…”
Section: Quimiocinas Do Receptor Cxcr3unclassified